O impacto das condições sociais na educação: um estudo de caso no colégio estadual Dr. Pedro Ludovico Teixeira/Porto Nacional – To - Viana, Katiele Cavalcante (Universidade Federal do Tocantins, 2021)
Studies on factors that interfere with school performance have been developed for more than five decades. In Brazil, studies on the state of education in the country intensified when the Basic Education Assessment System (SAEB) was established in 1995. It is important to understand the factors that may interfere in the educational performance of the students, thematic of academic relevance and of interest for public educational policies. In view of the foregoing, the present study aimed to evaluate the socioeconomic profile of the families of elementary and middle school students, to identify social factors that facilitate school disapproval and dropout, focusing on the family background of the students of the Colégio Estadual Dr. Pedro Ludovico Teixeira, municipality of Porto Nacional -TO. To analyze the socioeconomic profile, a semistructured questionnaire was sent to all the heads of the students of the College, so that they could respond. The indexes of approval, disapproval and abandonment were obtained through the notes of all the students participating in the research, made available by the College's secretariat. For data analysis, the students' answers were transferred to Excel and tabulated. the results obtained indicate that the problem of school dropout is more recurrent in High School and the failure in Elementary School. The low per capita income of families leads young people to work early, before finishing the studies. Yet, parents with limited training are not able to guide / accompany their children to help them overcome their limitations in schooling. Discouraged by the lack of opportunity / help, inside or outside the family, failure can become frequent, and drop-off the easier option for these students.